Bacterial succession of the digestive tract of a piglet fed with biological silage - Sánchez Súarez, Héctor (2019)
The composition and abundance of the bacterial microbiota in three portions of the gastrointestinal tract of a piglet, in the balanced feed and in biological ensilages prepared with residues of aquaculture origin were evaluated by metagenomic analysis. The DNA of the samples was extracted, and sequenced. The greatest bacterial diversity was in the balanced feed (44.7%), with the predominance of Candidatus phytoplasma surgarcane. In the biological silage predominated Lactobacillus casei and Lactococcus lactis. The existing diversity was similar between silage and the concentrate feed. Similarities were found between the bacteria of the three gastrointestinal regions (L. ultunensis, Selenomonas bovis, Prevotella copri, Enterococcus lactis y Campylobacter sp). In the stomach predominated Helicobacter rappini and Campylobacter coli, in the small intestine Selenomonas bovis and Lactobacillus ultunensis and in the rectum (faeces) Lactobacillus ultunensis and Prevotella copri.